Fuzzy Rule-Based System to Predict the Sustainability in Machining Process - V, Veeramani.; Sangeetha, M.; Mohamed, Roaa Adam Hussein; Dalton, G. Arul; Ramadass, Rajendra Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Industry 5.0 is the highly widespread version at present, with a time- and energy-efficient functioning procedure. Industry 5.0 focuses an immense value on augmented intelligence (AuI), which indicates both artificial and human intelligence are integrated in this industrial version. Industry 5.0 can promote environmentally friendly targets like durability, socio-environmental reliability, and human-centricity, extending outside the profit-centered effectiveness of Industry 4.0. For any industry to be worthwhile, the machine’s sustainability remains the top priority. This research article delivers a fuzzy rule-based strategy for Industry 5.0 which is a human-robot collaboration. The primary justification for adopting this fuzzy rule-based strategy in this machine sustainability forecast mechanism is that it is an If-Then rule-based reasoning method. This will offer an extremely precise and familiar prediction of sustainability in machining, enhancing industrial wealth while minimizing expenditure. The Augmented Intelligence (AuI) has turned popular recently in the industries given that when contrasted with industry 4.0, it is noticeable that industry 5.0 is persistently profitable, dependable, and offers greatest outcomes at a suitable hour. Any business will save time and money due to the manufacturing process rarely yields a significant level of waste and employs a sufficient quantity of input equipment. Consequently, this industrial 5.0 can deliver positive results without any losses thanks to its fuzzy rule-based method.